NGHIÊN CỨU LÂ P BIỂU THỂ TÍCH THÔNG BA LÁ (Pinus kesiya Royle ex.Gordon) Ở HÀ GIANG - Tuyến, Phạm Quang; Hằng, Bùi Thanh; Quý, Trần Hoàng; Phương, Nguyễn Thị Thu; Trung, Nguyễn Kim; Hưng, Nguyễn Quang (TẠP CHÍ KHOA HỌC LÂM NGHIỆP, 2024)
Từ khóa: TÓM TẮT (Pinus kesiya Royle ex.Gordon) ơ ế ị ơ V = 0 0000 *(D 2 H) 0,942 b 0 Kế ơ ọ